General solution of laplace and poisson equations in a multiply connected circular domain : Applications to torsion - Epele, Luis Nicolás (2012)
The general solution of Laplace and Poisson equations in multiply connected domains, in terms of the group of automorphism, is summarized. The particular application to the analysis of rods under torsion is presented. Different generalizations are discussed.